Analysis of Drug Accuracy, Dosage and Drug Interactions in Comorbid Hypertension COVID-19 Patients at Hospital X in Central Java Period 2021 - Khairani, Sondang; Manninda, Reise; Fajri Rosyiedi, Afif (International Journal of Scientific Research and Management (IJSRM), 2022)
Treatment of COVID-19 comorbid hypertension involves many drugs with therapeutic risk of non-guidelines and potential drug interactions. Study aimed to determine the demographic characteristics, clinical degree, accuracy of drugs and doses and potential drug interactions. Study design was cross-sectional through retrospective data collection. Samples that meet the criteria obtained 70 samples. The results were 51.4% female sample, the highest age was 46-59 y.o (48.6%), the most degree of COVID-19 was moderate (61.4%), the highest degree of hypertension was grade 1 (48.6%) and the longest length of stay was >14 days (51.4%). The accuracy of COVID-19 therapy were 78.6% accurate drug, 21.4% inaccurate drug, and 100% accurate dose. The accuracy of antihypertensive were 82.9% accurate drug, 17.1% inaccurate drug, 95.7% accurate dose and 4.3% inaccurate dose. Samples with potential drug interactions were 97.1%, the highest number of potential drug interactions was 1-5 events (52.9%), based on severity 60.2% moderate, 20.1% minor, 13.2% major, and 6.5% unknown. Correlation test results sig. (p-value) 0.237. The conclusion showed that most samples were female, aged 46-59, moderate-grade COVID-19 patients with grade 1 hypertension, and length of stay >14 days. There is accuracy or inaccuracy of drugs and doses, potential drug interactions and there is no relationship between length of stay and potential drug interactions.